The art of deception: trust and deception in sender-receiver dynamics - Hu, Huiying (Nanyang Technological University, 2024)
The production and distribution of false information has been progressively economised by technological advancements, increasing its scope and impact. To effectively combat false information with limited resources, it is important to prioritise efforts on successful deception attempts. From this perspective, we examined the conditions under which receivers were more likely to accept false information, focusing on the trustworthiness of senders. We operationalised sender trustworthiness as the frequency at which a sender has provided accurate signals in the past. To investigate this, we conducted an online experiment where 1,023 participants were tasked with solving 30 arithmetic problems, each with four options, under time constraints. Within each problem, one option was highlighted. Source accuracy, or in this case, proportions at which the highlighted option was the correct option, ranged from 0 to 80%. Our findings revealed that higher source accuracy crucially increases a receiver’s likelihood of accepting a source’s signals while reducing deception opportunities, restricting the number of potentially successful deception attempts. This paradoxically suggests that honesty plays a crucial role in facilitating successful deception. The paper concludes with a discussion of the potential implications of our findings and suggestions for future research.